EVALUASI KEBIJAKAN PENATAAN PASAR JOHAR, PASAR BULU DAN PASAR JATINGALEH - Heryandini Novendasyarizky; Ahmad Taufiq; Purwoko . (Journal of Politic and Government Studies, 2014)
ABSTRACTThis study was conducted to explain the results of an evaluation The Development Program ofJohar’s market, Bulu’s market, and jatingaleh’s market which held by Semarang Government’s city,Semarang city council market, UPTD johar’s Market, UPTD Bulu’s Market and UPTD Jatingaleh’sMarket within period of 2009-2011. The Program motivation start by increasingly the poor quality oftraditional market in Semarang. The purpose of this program is to restore the functions of traditionalmarket into a modern semi market that clean, safe, comfort, and tidy.In order to explain the evaluation of implementation, management, and accountability fromthis development program of Johar’s market, Bulu’s Market and Johar’s market, the research is usingqualitative method. The subject of this study is semarang city council market, UPTD johar’s Market,UPTD Bulu’s market, UPTD Jatingaleh’ market, as well as consument and the owner of the stall/ kioskin each market. The data collection method such as interviews, observation, document investigation,and questionnaires using random sampling method.The result of this Research explained in 2009, Goverment city together with Semarang citycouncil market, UPTD Johar’s Market, UPTD Bulu’s market, and UPTD Jatingaleh’s market formedthe Development program for various traditional markets such as Johar’s Market, Bulu’s Market, andJatingaleh’s Market. This Development program increase positive results including Building renovationto previous functions. In line with the holding of this program, there are some obstacles in theimplementation of this program, they are lack of interest from the owner to support and participationfor this development program, moreover the constrained funding allocations intended for theconstruction of Johar market. Meanwhile, The society strongly agrees with the Development Programfor Johar’s Market, Bulu’s Market, and Jatingaleh’s market.It is rerecommended for future research to prepare adequate funding before starting theimplementation of development program for Johar’s Market, Bulu’s Market, and Jatingaleh’s market .So that, the results achieve maximum point and to fulfill customers wishes for comfort, save, clean, andtidy’s traditional market.Kata kunci : The Development Program, Tradisional Market, Johar’s market, Bulu’s market, andJatingaleh’s market